Nfu facilitates the maturation of iron‐sulfur proteins and participates in virulence in Staphylococcus aureus. Issue 3 (20th December 2014) - Mashruwala, Ameya A.; Pang, Yun Y.; Rosario‐Cruz, Zuelay; Chahal, Harsimranjit K.; Benson, Meredith A.; Mike, Laura A.; Skaar, Eric P.; Torres, Victor J.; Nauseef, William M.; Boyd, Jeffrey M.
Summary The acquisition and metabolism of iron (Fe) by the human pathogen Staphylococcus aureus is critical for disease progression. S. aureus requires Fe to synthesize inorganic cofactors called iron‐sulfur (Fe‐S) clusters, which are required for functional Fe‐S proteins. In this study we investigated the mechanisms utilized by S. aureus to metabolize Fe‐S clusters. We identified that S. aureus utilizes the Suf biosynthetic system to synthesize Fe‐S clusters and we provide genetic evidence suggesting that the sufU and sufB gene products are essential. Additional biochemical and genetic analyses identified Nfu as an Fe‐S cluster carrier, which aids in the maturation of Fe‐S proteins. We find that deletion of the nfu gene negatively impacts staphylococcal physiology and pathogenicity. A nfu mutant accumulates both increased intracellular non‐incorporated Fe and endogenous reactive oxygen species (ROS) resulting in DNA damage. In addition, a strain lacking Nfu is sensitive to exogenously supplied ROS and reactive nitrogen species. Congruous with ex vivo findings, a nfu mutant strain is more susceptible to oxidative killing by human polymorphonuclear leukocytes and displays decreased tissue colonization in a murine model of infection. We conclude that Nfu is necessary for staphylococcal pathogenesis and establish Fe‐S cluster metabolism as an attractive antimicrobial target.